Influence of high temperatures on the adhesion of epoxy to hardened mortar or fresh cement mortar and steel plate - Aguiar, J. L. Barroso de (1999)
Epoxies are a kind of polymers which present high adhesion to various materials. The use of epoxies in construction has become very important, especially in repair works, bond of precast elements and construction joints. Like all the polymers, epoxies have low thermal resistance. Therefore, it is expected that the bonds with this polymer can not resist at high temperatures. In this paper, we present the results of an experimental work made with specimens of normal hydraulic mortar. Three kinds of bonds with two kinds of epoxies were tested. We bonded hardened mortar/hardened mortar, hardened mortar/fresh mortar and hardened mortar/steel plate. Seven days after bonding, the specimens were exposed to mperatures between 20 and 200 ºC. The duration of exposure was seven days. To determine the adhesion, we used flexure strength tests. The results of the tests show that above 100 ºC we have significant decrease of adhesion strength. Between 20 and 100 ºC, mortar failures were observed. Above 100 ºC, we had adhesive failures in the greater part of the tests.